2007
DOI: 10.1016/j.critrevonc.2007.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting receptor tyrosine kinase signaling in acute myeloid leukemia

Abstract: Targeting receptor tyrosine kinase signaling in acute myeloid leukemia The main goal of this work was therefore aimed at gaining deeper insight into RTK signaling in a panel of AML cell lines and patient blast cells. A broad potein expression analysis was set up in order to identify cancer-specific expression patterns of signaling molecules and to uncover potential molecular targets. Using different approaches the molecular function and the feasibility of targeting the candidate proteins was investigated. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 213 publications
(272 reference statements)
1
44
0
2
Order By: Relevance
“…In malignant hematologic disease, PI3K signaling is most likely activated by oncogenic mutations of upstream regulators such as tyrosine kinases and Ras (38) and/or autocrine growth factor loops (21). Of the different PI3K isoforms, it has been shown that p110y plays an important role in cell proliferation, survival, and chemoresistance in AML (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In malignant hematologic disease, PI3K signaling is most likely activated by oncogenic mutations of upstream regulators such as tyrosine kinases and Ras (38) and/or autocrine growth factor loops (21). Of the different PI3K isoforms, it has been shown that p110y plays an important role in cell proliferation, survival, and chemoresistance in AML (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that two major genetic events are involved in leukemic transformation. 30 The core of this theory is that two separate mutations or two groups of mutations must arise at approximately the same time for leukemia to develop. One mutation leads to the proliferation of the hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…A sample in PBS buffer was loaded into a quartz cuvette and analyzed with a 488 nm laser. Fifty spectra were collected at 25 C to estimate diffusion coefficient and relative polydispersity. Data were analyzed with Dynamics software V.5.25.44 (Protein Solutions) and vesicle size was measured as the mean hydrodynamic radius.…”
Section: Dynamic Light Scattermentioning
confidence: 99%